Metabolic reconstructions identify plant 3‐methylglutaconyl‐CoA hydratase that is crucial for branched‐chain amino acid catabolism in mitochondria. (12th June 2018) - Latimer, Scott; Li, Yubing; Nguyen, Thuong T.H.; Soubeyrand, Eric; Fatihi, Abdelhak; Elowsky, Christian G.; Block, Anna; Pichersky, Eran; Basset, Gilles J.
Summary: The proteinogenic branched‐chain amino acids (BCAAs) leucine, isoleucine and valine are essential nutrients for mammals. In plants, BCAAs double as alternative energy sources when carbohydrates become limiting, the catabolism of BCAAs providing electrons to the respiratory chain and intermediates to the tricarboxylic acid cycle. Yet, the actual architecture of the degradation pathways of BCAAs is not well understood. In this study, gene network modeling in Arabidopsis and rice, and plant‐prokaryote comparative genomics detected candidates for 3‐methylglutaconyl‐CoA hydratase (4.2.1.18), one of the missing plant enzymes of leucine catabolism. Alignments of these protein candidates sampled from various spermatophytes revealed non‐homologous N‐terminal extensions that are lacking in their bacterial counterparts, and green fluorescent protein‐fusion experiments demonstrated that the Arabidopsis protein, product of gene At4g16800, is targeted to mitochondria. Recombinant At4g16800 catalyzed the dehydration of 3‐hydroxymethylglutaryl‐CoA into 3‐methylglutaconyl‐CoA, and displayed kinetic features similar to those of its prokaryotic homolog. When at4g16800 knockout plants were subjected to dark‐induced carbon starvation, their rosette leaves displayed accelerated senescence as compared with control plants, and this phenotype was paralleled by a marked increase in the accumulation of free and total leucine, isoleucine and valine. The seeds of the at4g16800 mutant showed a similar accumulation of free BCAAs. These data suggest that 3‐methylglutaconyl‐CoA hydratase is not solely involved in the degradation of leucine, but is also a significant contributor to that of isoleucine and valine. Furthermore, evidence is shown that unlike the situation observed in Trypanosomatidae, leucine catabolism does not contribute to the formation of the terpenoid precursor mevalonate. Significance Statement: 3‐methylglutaconyl‐CoA hydratase is one of the 'missing' plant enzymes for the catabolism of leucine, an essential amino acid for vertebrates. The cognate pathway also serves as a vital energy source for plant tissues when carbohydrate availability is restricted.